INTEGRASI ILMU LUGHAH DAN FIQIH LUGHAH: ANALISIS EPISTEMOLOGIS DALAM KAJIAN BAHASA ARAB KONTEMPORER - Hayatun Nissa; Dika Syam El-Fatony; Afif Amrulloh (Makkah: Journal Of Islamic Studies, 2025)
This article aims to examine in depth the concepts of ‘Ilm al-Lughah (Arabic Linguistics) and Fiqh al-Lughah (Philosophy of Language) as two important disciplines in Arabic language studies. ‘Ilm al-Lughah focuses on the linguistic study of Arabic from the aspects of phonology, morphology, syntax, to semantics. In contrast, Fiqh al-Lughah emphasizes the philosophical aspects of language, vocabulary development, and the relationship between language and culture and thought. The two are closely interrelated in forming a comprehensive understanding of the Arabic language, both in academic and practical realms. This research uses a qualitative approach with a literature review method by analyzing various classical and contemporary literature. The study's results indicate that ‘Ilm al-Lughah and Fiqh al-Lghah are inseparable in developing Arabic linguistic science. Their synergy is highly relevant in addressing the challenges of language modernization, Arabic language teaching, and the integration of Islamic sciences.